Effectiveness in Space and Energy Utilization in Hvac System Selection - Elbiz, Gizem; Başaran, Tahsin (Izmir Institute of Technology, 2019)
In Turkey, energy consumption for heating constitutes an important part of the total energy consumed. The choice of heating system and the preferences in the use of related energy sources, excessive energy consumption and environmental impact cause high costs and significant area losses. A large number of parameters must be evaluated for the correct system selection. These parameters determine the installation cost of the system, heating and cooling loads during the construction period, and the environmental impact of energy consumption. This study aims to obtain the most economical and environmental friendly energy resource in a housing structure and accordingly, heating system and the system spatial value. The use of fossil fuels such as coal, fuel oil and natural gas and the geothermal energy as a renewable energy source are planned to be investigated. The analysis was carried out on how the climate conditions and economic values of the provinces of İzmir, Balıkesir, Kütahya and Ağrı, which are located in different climatic regions will be effected and where direct use of geothermal energy is concerned, will affect the results of the different system usage. Life Cycle Cost assessment was performed to investigate the relationship between the initial investment in a housing structure and the use of energy source and system selection. Geothermal energy is the best source of energy both for installation and renewal and for fuel consumption and environmental purposes. Geothermal heat exchangers selected for the source take up 36 times less space than coal boilers, and the economic reflection of this area is approximate 8000 if given the example of İzmir province. While considering the environmental impacts, CO2 emissions of geothermal energy are 15 times less than natural gas and 50 times less than coal.

Ülkemizde ısıtma amaçlı enerji tüketimi, tüketilen toplam enerjinin önemli bir kısmını oluşturmaktadır. Isıtma sistem seçimi ve ilgili enerji kaynaklar kullanımındaki tercihler, enerji tüketiminin ve çevresel etkilerinin fazla olması, yüksek maliyetlere ve büyük alan kayıplarına neden olmaktadır. Doğru sistem seçimi için, çok sayıda parametrenin değerlendirilmesi gerekir. Bu parametreler sistemin kurulum maliyetini, yapı ömrü boyunca ısıtma ve soğutma yüklerini ve enerji tüketimi ile çevresel etkilerini belirlemektedir. Bu çalışma, bir konut yapısında en ekonomik ve çevreci enerji kaynağını ve buna bağlı olarak ısıtma sistemini ve sistem mekânsal karşılığını elde etmeyi amaçlamıştır. Konutların ısıtılmasında fosil yakıtlardan olan kömür, fuel oil ve doğalgaz ile jeotermal yenilenebilir enerji kaynağının kullanımının araştırılması planlanmıştır. Farklı iklim bölgelerinde yer alan ve jeotermal enerjinin direkt kullanımının söz konusu olduğu İzmir, Balıkesir, Kütahya ve Ağrı illerinin iklim koşulları ile ekonomik değerlerinin, farklı sistem kullanımından kaynaklanan sonuçları ne kadar etkileyeceği üzerine analizler yapılmıştır. Bir konut yapısına yapılan ilk yatırım ile enerji kaynağının ve sistem seçim kullanımı arasındaki ilişkiyi Yaşam Döngüsü Maliyet analizi göstermiştir. Jeotermal enerjinin hem kurulum ve yenileme hem yakıt tüketim maliyeti hem de çevresel açıdan en iyi enerji kaynağı olduğu görülmüştür. Jeotermal kaynak için seçilen ısı eşanjörleri kömür kazanlarına göre 36 kat daha az yer kaplamakta, bu alanın ekonomik yansıması İzmir ili için örneğin yaklaşık 8000$ olmaktadır. Jeotermal enerjisinin çevresel etkileri düşünüldüğünde ise CO2 emisyonu kömüre göre 50 kat, doğalgaza göre 15 kat daha azdır.
Isıtma Soğutma ve Havalandırma Sistem Seçiminde Enerji ve Mekan Kullanım Etkinliği
Thesis (Master)--Izmir Institute of Technology, Architecture, Izmir, 2019
Includes bibliographical references (leaves: 111-115)
Text in English; Abstract: Turkish and English
Keywords: HVAC systems; Energy consumption; Climate conditions; Environmental factors; Geothermal energy